Mixed Phenotype Acute Leukemias - Gao, MD, PhD, Chen; Sands, MD, Amy M.; Sun, MD, PhD, Jianlan (North American Journal of Medicine and Science, 2012)
Mixed phenotype acute leukemia represents a small subset of acute leukemia that cannot be simply assigned as myeloid or lymphoid lineage, because of the ambiguous phenotype the leukemic cells exhibit. It encompasses leukemias containing separate populations of blasts of more than one lineage, or a single population of blasts co-expressing antigens of more than one lineage. The 2008 World Health Organization classification established strict criteria for diagnosis of mixed phenotype acute leukemia, emphasizing myeloperoxidase for myeloid lineage assignment, cytoplasmic CD3 for T lineage assignment, and CD19 and other B markers for B lineage assignment. A variety of cytogenetic lesions have been identified in this group of diseases, two of which, the t(9;22)(q34;q11) BCR-ABL1 translocation, and t(v;11q23) with MLL rearrangement are considered separate entities. Other categories include T/myeloid NOS, B/myeloid NOS and other rare types. Mixed phenotype acute leukemia is associated with poor outcome compared with other types of acute leukemias, particularly in those with Philadelphia chromosome, and clinically presents challenges in diagnosis and treatment.